TCM codes for fading mobile channels - Lim, Kee Chai. (2008)
Optimum trellis codes for a given complexity (constraint length or number of states) were found by Ungerboeck [1]. He applied a technique called "set partitioning" for coding of band-limited channels. The major drawback of this work is that each signal configuration seemed to require a different code, so that no single encoder-decoder could be used for a wide set of parameters. Viterbi proposed a remedy for this drawback by introducing a pragmatic approach to trellis-coded modulation [2]. However, the parallel branches in the trellis diagram of the Pragmatic code indicate a constraint in applying the pragmatic approach for fading mobile channels.